Revitalisasi Civic Disposition Dalam Menumbuhkan Nilai-Nilai Pancasila Di Sekolah Dasar - Irwan, Irwan (Universitas Pahlawan Tuanku Tambusai, 2021)
The research aims to identify and develop the revitalization of civic disposition in fostering the values of Pancasila at SDN 3 Nganganaumala. The research design used a qualitative research type with a qualitative descriptive approach. The subjects used as samples in this study were students, educators, school leaders and parents, totaling 52 people. Research data collection was carried out by observation, interview and documentation techniques. Data analysis used an interactive model consisting of sorting data, describing the data and interpreting conclusions. The results showed that the revitalization of civic disposition in fostering the values of Pancasila in SDN 3 Nganganaumala from all the participants had different answers and experiences consisting of the competence of role models for good students, a conducive and meaningful will given to students , habits of self-respect and integration of school members in fostering morality. The conclusion from research in the revitalization of civic disposition fosters the values of Pancasila, all school residents and parents who have been applied in schools have a good effect.